Clinical validity of new genetic biomarkers of irinotecan neutropenia: an independent replication study - Crona, DJ (Pharmacogenomics J, 2015)
The overall goal of this study was to provide evidence for the clinical validity of nine genetic variants in five genes previously associated with irinotecan neutropenia and pharmacokinetics. Variants associated with absolute neutrophil count (ANC) nadir and/ or irinotecan pharmacokinetics in a discovery cohort of cancer patients were genotyped in an independent replication cohort of 108 cancer patients. Patients received single-agent irinotecan every 3 weeks. For ANC nadir, we replicated UGT1A1*28, UGT1A1*93 and SLCO1B1*1b in univariate analyses. For irinotecan area under the concentration–time curve (AUC(0-24)), we replicated ABCC2 -24C>T; however, ABCC2 -24C>T only predicted a small fraction of the variance. For SN-38 AUC(0-24) and the glucuronidation ratio, we replicated UGT1A1*28 and UGT1A1*93. In addition to UGT1A1*28, this study independently validated UGT1A1*93 and SLCO1B1*1b as new predictors of irinotecan neutropenia. Further demonstration of their clinical utility will optimize irinotecan therapy in cancer patients.